Distribution and abundance of Oncaea media and O. venusta (Crustacea: Copepoda) in the Colombian Pacific Ocean During two periods in 2001 (2015)
Zooplankton of the Colombian Pacific Ocean was investigatedduring June-July (2001a) and August-September (2001b). Since Oncaea venusta and O. media predominated in the copepod community, their distribution and abundance were evaluated. Organisms were extracted from surface mesozooplankton samples taken with a conic net (50cm opening, 363μm mesh). Both species were widely distributed with highest abundances mainly in neritic waters (3°-5°N).Factor analysis revealed negative and positive correlations among abundances and abiotic variables depending on each period. Cluster analysis showed three groups in 2001a and five ones in 2001b, essentially consistent with night and day abundances, and thermocline depth and width suggesting the influence of these factors on O. venusta and O. media. In future analysis it may be necessary to consider the different forms of O. media and O. venusta to establish the importance of phytoplankton and other organisms in their diet. Higher night or day abundances allude to the possible diel vertical migration of these microcrustaceans to the surface. The decrease in the general abundance of O. venusta from 2001a to 2001b (66.4% to 47.5%) contrasted with the increase of O. media (33.6% to 52.5%). These changes could be explained by the different biological response of both species to short-term variability in oceanographic conditions and the occurrence of a weak La Niña event.